PERTIMBANGAN PENENTU PENUMPANG SAAT MEMILIH JASA TRANSPORTASI KAPAL LAUT PADA PT DHARMA LAUTAN UTAMA CABANG PONTIANAK - Lim, Andry Lindi (MABIS, 2013)
Transportation today has become a very vital thing in supporting the mobility of people in carrying out activities either through land, sea, or air. The purpose of this study was to determine the factors considered in choosing the passenger transport ships. The method used is descriptive research method of collecting data through observation, questionnaires, interviews and documentary studies. Collection methods using incidental sampling with a sample of 100 respondents. Data analysis was descriptive and qualitative research are based on the five dimensions of service quality, namely reliability, responsiveness, assurance, empathy and tangibles. Data and information obtained were analyzed using percentage calculations, only then the conclusion can be drawn. The results obtained from this study is the marketing policy relating to the attributes of service quality dimensions most respondents agreed. Advice authors are company should continue to monitor the trends that existed at the time the passenger is what can attract the attention of prospective customers of potential services for the company, so it is not glued to the coverage of the market that has been achieved by the company. Promotion should be owned by the company needs to be improved further by conducting promotional programs that are more innovative and creative in order to keep passengers loyal to the company.